High Mobility Group Box 1 and TLR4 Signaling Pathway in Gnotobiotic Piglets Colonized/Infected with L. amylovorus, L. mucosae, E. coli Nissle 1917 and S. Typhimurium - Splichal, Igor (Int J Mol Sci, 2019)
High mobility group box 1 (HMGB1) is a DNA-binding nuclear protein that can be actively secreted by immune cells after different immune stimuli or passively released from cells undergoing necrosis. HMGB1 amplifies inflammation, and its hypersecretion contributes to multiple organ dysfunction syndrome and death. We tested possible immunomodulatory effect of commensal Lactobacillus amylovorus (LA), Lactobacillus mucosae (LM) or probiotic Escherichia coli Nissle 1917 (EcN) in infection of gnotobiotic piglets with Salmonella Typhimurium (ST). Transcription of HMGB1 and Toll-like receptors (TLR) 2, 4, and 9 and receptor for advanced glycation end products (RAGE), TLR4-related molecules (MD-2, CD14, and LBP), and adaptor proteins (MyD88 and TRIF) in the ileum and colon were measured by RT-qPCR. Expression of TLR4 and its related molecules were highly upregulated in the ST-infected intestine, which was suppressed by EcN, but not LA nor LM. In contrast, HMGB1 expression was unaffected by ST infection or commensal/probiotic administration. HMGB1 protein levels in the intestine measured by ELISA were increased in ST-infected piglets, but they were decreased by previous colonization with E. coli Nissle 1917 only. We conclude that the stability of HMGB1 mRNA expression in all piglet groups could show its importance for DNA transcription and physiological cell functions. The presence of HMGB1 protein in the intestinal lumen probably indicates cellular damage.